2006
DOI: 10.1007/s11864-006-0050-5
|View full text |Cite
|
Sign up to set email alerts
|

Selection of optimal adjuvant endocrine therapy for early-stage breast cancer

Abstract: Oophorectomy was found to cause regression of advanced breast cancer toward the end of the 19th century. Decades later, the discovery that estrogen plays a central role in this process eventually led to two important consequences: first, different modalities were developed to suppress or antagonize estrogen; and second, the ability to detect estrogen receptor in breast cancer tissue became a predictor of response to treatment--probably the best marker for response among all solid tumors. Tamoxifen, which works… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Although standard chemotherapy kills most cells in a tumor, cancer stem cells remain viable [29][30][31][32]. This model is consistent with some clinical observations.…”
Section: Cancer Stem Cellssupporting
confidence: 83%
“…Although standard chemotherapy kills most cells in a tumor, cancer stem cells remain viable [29][30][31][32]. This model is consistent with some clinical observations.…”
Section: Cancer Stem Cellssupporting
confidence: 83%
“…Estrogen, for example, can stimulate breast cancer cell proliferation and survival directly, but can also indirectly stimulate tumor growth by promoting tumor angiogenesis (60–63). Oophorectomy or pharmacologic strategies that reduce estrogen receptor signaling can promote regression of hormone receptor‐positive tumor cells (64–67). Endocrine therapy does not completely eliminate tumor cells but can produce long‐term remission when combined with other forms of therapy such as surgery.…”
Section: Cell Cycle Arrestmentioning
confidence: 99%
“…In breast tissue, tamoxifen acts as an estrogen antagonist and competitively inhibits estrogen binding to ERs, which blocks the actions of estrogen on breast cancer cells (6). Recent investigations have shown that tamoxifen promptly stimulates the activation of ERK1/2 in an ER-positive breast cancer cell line (MCF-7) (7), and this causes both cell-cycle arrest and apoptosis via an induction of signaling that leads to a modulation of the MAPK and mitochondria/caspase pathways in breast cancer cells (8).…”
mentioning
confidence: 99%